Added Value of Spectroscopy to Perfusion MRI in the Differential Diagnostic Performance of Common Malignant Brain Tumors - Vallée, A.; Guillevin, C.; Wager, M.; Delwail, V.; Guillevin, R.; Vallée, J.-N. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Perfusion and spectroscopic MR imaging provide noninvasive physiologic and metabolic characterization of tissues, which can help in differentiating brain tumors. We investigated the diagnostic role of perfusion and spectroscopic MR imaging using individual and combined classifiers of these modalities and assessed the added performance value that spectroscopy can provide to perfusion using optimal combined classifiers that have the highest differential diagnostic performance to discriminate lymphomas, glioblastomas, and metastases.MATERIALS AND METHODS: From January 2013 to January 2016, fifty-five consecutive patients with histopathologically proved lymphomas, glioblastomas, and metastases were included after undergoing MR imaging. The perfusion parameters (maximum relative CBV, maximum percentage of signal intensity recovery) and spectroscopic concentration ratios (lactate/Cr, Cho/NAA, Cho/Cr, and lipids/Cr) were analyzed individually and in optimal combinations. Differences among tumor groups, differential diagnostic performance, and differences in discriminatory performance of models with quantification of the added performance value of spectroscopy to perfusion were tested using 1-way ANOVA models, receiver operating characteristic analysis, and comparisons between receiver operating characteristic analysis curves using a bivariate χ2, respectively.RESULTS: The highest differential diagnostic performance was obtained with the following combined classifiers: maximum percentage of signal intensity recovery–Cho/NAA to discriminate lymphomas from glioblastomas and metastases, significantly increasing the sensitivity from 82.1% to 95.7%; relative CBV–Cho/NAA to discriminate glioblastomas from lymphomas and metastases, significantly increasing the specificity from 92.7% to 100%; and maximum percentage of signal intensity recovery–lactate/Cr and maximum percentage of signal intensity recovery–Cho/Cr to discriminate metastases from lymphomas and glioblastomas, significantly increasing the specificity from 83.3% to 97.0% and 100%, respectively.CONCLUSIONS: Spectroscopy yielded an added performance value to perfusion using optimal combined classifiers of these modalities, significantly increasing the differential diagnostic performances for these common brain tumors.AUCarea under the ROC curveΔR2*relaxation rateGBMhigh-grade gliomas (glioblastomas)LaclactateLiplipidsmaxmaximumminminimumPCNSLprimary central nervous system lymphomaPRESSpoint-resolved spectroscopic sequencePSRpercentage of signal intensity recoveryrCBVrelative cerebral blood volumeROCreceiver operating characteristic